Budgeting during austerity: Approaches, instruments and practices - Ringa Raudla (Budgetary Research Review (BRR), 2013)
The recent global financial and economic crises, followed by fiscal crisis, have led many governments in Europe to adopt austerity measures in order to cope with the concurrent problems of lower revenues and high public debt. It can be expected that the need to undertake large-scale cutbacks would lead to changes in budgeting practices, budgetary institutions and modes of fiscal governance. Based on the existing literature on fiscal governance and budgeting, it can be conjectured that in response to fiscal stress, the following shifts have taken (or are taking) place in fiscal governance and budgetary institutions: movement from decentralized and bottom-up modes of budget preparation to centralized and top-down modes, adoption of numerical fiscal rules, and the revival of the 'more rational' budgetary decision-making techniques (e.g., performance-based budgeting, results-based budgeting, etc.).
Keywords: 330